2009
DOI: 10.1177/0267659109106773
|View full text |Cite
|
Sign up to set email alerts
|

Bioline® heparin-coated ECMO with bivalirudin anticoagulation in a patient with acute heparin-induced thrombocytopenia: the immune reaction appeared to continue unabated

Abstract: Heparin-induced thrombocytopenia (HIT) is a serious, antibody-mediated complication of heparin which significantly confers risks of thrombosis and devastating outcomes. Once diagnosed, it requires immediate cessation of heparin and therapy with an alternative anticoagulant. No data are available in the literature on the pathophysiology and clinical implications of performing prolonged extracorporeal membrane oxygenation with a heparin-coated system in a patient with acute HIT treated with bivalirudin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 5 publications
0
60
2
1
Order By: Relevance
“…Routine monitoring of head ultrasounds did not reveal intracranial hemorrhage in any of the 12 subjects while on bivalirudin. Two subjects had evidence of hemorrhage from chest tubes requiring chest (19)(20)(21)(22)(23)(24). Therefore, clinicians are confronted with the perilous challenge of non-heparin anticoagulation for this complex patient population with minimal evidence or guidance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine monitoring of head ultrasounds did not reveal intracranial hemorrhage in any of the 12 subjects while on bivalirudin. Two subjects had evidence of hemorrhage from chest tubes requiring chest (19)(20)(21)(22)(23)(24). Therefore, clinicians are confronted with the perilous challenge of non-heparin anticoagulation for this complex patient population with minimal evidence or guidance.…”
Section: Resultsmentioning
confidence: 99%
“…There are several cases describing the use of alternative direct thrombin inhibitors (argatroban, lepirudin) during extracorporeal life support including three case reports and one case series using bivalirudin (19)(20)(21)(22)(23)(24). This analysis describes the dosing and monitoring of bivalirudin as an alternative to heparin in pediatric extracorporeal life support patients who developed heparin-induced thrombocytopenia, heparin resistance, or significant thrombosis while on heparin.…”
mentioning
confidence: 99%
“…However, it has been shown previously that even small quantities of heparin in the circuit coating may be responsible for deleterious effects when HIT has been triggered. 11 In addition, the extracorporeal circuit has an impact on the pharmacokinetics of the drugs because of the increased volume distribution. 13 The drug's adsorption on the different components of the circuit is often difficult to estimate, and it adds further complexity to the determination of pharmacokinetic parameters of patients treated with ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…11,14,15 One recent study 16 systematically analyzed a sample of 21 patients receiving bivalirudin during VA postcardiotomy ECMO. Ranucci et al 16 found that bivalirudin can be used safely and effectively to limit bleeding and allogeneic blood product transfusions in these patients, even if a superiority of bivalirudin versus heparin could not be shown.…”
Section: Discussionmentioning
confidence: 99%
“…14 In medicinal chemistry, many compounds containing pyrazole moiety have exhibited biological activity, 16 such as apixaban (Figure 1), 17 which has been approved for the treatment of venous thromboembolism, 18 revealing the potential of pyrazole derivatives as promising for the inhibition of coagulation factors such as thrombin or FXa. Many successful anticoagulants, such as the direct thrombin inhibitors argatroban (Figure 1), chosen as treatment of patients with heparin induced thrombocytopenia, 19 and dabigatran etexilate (Figure 1), used for multiple thromboembolic disease indications, 20 are highly water-soluble, poorly absorbable and direct thrombin inhibitors. 21,22 Such features are mainly due to the presence of charged groups able to make the molecular structure highly hydrated and water-soluble.…”
mentioning
confidence: 99%